Uma opção terapêutica para o aumento da faixa de gengiva inserida: o enxerto de tecido conjuntivo livre - Borges Filho, Fausto Frizzera [UNESP]; Molon, Rafael de Scaf [UNESP]; Verzola, Mario de Arruda [UNESP]; Rached, Ricardo Samih Georges Abi [UNESP]; Sampaio, José Eduardo Cezar [UNESP]; Orrico, Silvana Regina Perez [UNESP] (My University, 2012)
Several periodontal procedures have been described in the literature to correct mucogingival alterations or to achieve root coverage. The epithelized free gingival graft is a well established periodontal surgery to increase the width of keratinized gingiva with good stability in the long term follow up. However, this procedure is not commonly used in aesthetic areas since the grafted tissue presents differences of color and contrast. The free connective tissue graft emerges as a viable option to increase attached gingiva in areas where aesthetics results are required. The removal of an epithelized free gingival graft from the hard palate region creates a sore and raw surgical wound that slowly repairs, while the connective tissue graft produces only a line of incision that can be easily sutured promoting a more confortable outcome for the patient. This paper aims to report a case where a free connective tissue graft was used to increase the width of attached gingiva in a tooth with gingival recession. This technique presented satisfactory esthetics results, with a better contrast and color matching with the surrounding tissues.

Uma ampla variedade de procedimentos cirúrgicos periodontais tem sido descrita na literatura para correção de problemas mucogengivais e para cobertura radicular. O enxerto gengival livre epitelizado é um procedimento bem estabelecido para aumentar a faixa de gengiva ceratinizada, com resultados favoráveis em longo prazo. Entretanto, este procedimento não é comumente utilizado em regiões estéticas, pois o tecido enxertado apresenta diferença de cor e contraste com os tecidos adjacentes. Neste sentido, o enxerto de tecido conjuntivo livre surge como uma opção viável para aumento de gengiva inserida em regiões onde a demanda estética é necessária. Enquanto que a remoção do enxerto gengival livre da região do palato duro cria uma área cruenta e dolorida que demora a reparar, a do enxerto de tecido conjuntivo produz apenas uma área de incisão facilmente suturada, sendo mais confortável ao paciente. Sendo assim, o objetivo do presente relato foi apresentar um caso clínico tratado com a técnica de enxerto gengival livre de tecido conjuntivo para aumento da quantidade de gengiva inserida em um dente com recessão gengival. No caso apresentado, a técnica de enxerto conjuntivo livre apresentou resultados estéticos satisfatórios, com melhor coloração e contraste com os tecidos adjacentes.
A therapeutic option to increase attached gingiva: the free connective tissue graft
Keywords: Gingival recession; Esthetics; Attached gingiva; Free connective tissue graft; Recessão gengival; Estética; Gengiva inserida; Enxerto de tecido conjuntivo livre